Spatial and temporal patterns of a generalist urban carnivore; American black bears (Ursus americanus) at Lake Tahoe (CA) - Klip, Mario (eScholarship, University of California, 2018)
Human populations are growing and exert an increasing pressure on remaining wild habitats. Development and encroachment into wild habitats often create a wildland-urban interface. Understanding how and which species are able to persist or even flourish in these shared habitats, is important for conservation purposes and reducing human-wildlife conflict. Human-wildlife conflict may be of particular concern when it involves larger carnivores. Urban wildlife involved in conflict sometimes may be considered to have a lesser ecological value than its wild counterparts. This is particularly the case when animals are thought to be reliant on garbage and other human-provided food sources. However, as wild habitats shrink, wildlife cannot be exclusively preserved in remote wilderness settings. The American black bear (Ursus americanus) is a good example of an adaptable animal that is able to thrive in human-modified habitats but consequently is involved in high levels of reported bear-human conflict. Black bears are not endangered in most of their range, but lessons learned from this charismatic animal are likely applicable in deeper conservation contexts. In this dissertation, I attempted to better understand what it means to be classified as an urban animal, how spatial distributions and resource selection might vary between urban and wild areas, how drought might affect distributions, and how bear behavior might be influenced through human induced stimuli.First, despite its ubiquitous use, the term “urban” was not homogenous throughout the scientific literature and needed to be defined. Spatially defined urban extents have great influence on whether wildlife is deemed urban or not. This was even more important because the prevailing paradigm prior to this study was that black bears observed in urban areas were spending the majority of their time in this habitat. From 2010-2014, I outfitted 27 bears with GPS Iridium radio collars in Lake Tahoe to understand spatial usage. I assessed existing urban definitions and tried to define the most conservative definition that would include human development in the broadest sense. I assessed whether bears were spending 50% or more of their time in urban areas, if they did I considered them urban. During 2010-2011 no bears spent ≥50% of their time in urban areas; during 2012 25% of the bears spent ≥50% of their time in urban areas, whereas during 2013, 2014 and 2015 half of the bears spent ≥50% or more of their time in urban areas. Additionally, I assessed preference at three different orders (scales). While bears appeared to prefer urban habitats at first order (defined as the study area), they generally did not select urban habitats within their home range (second order). Further, I evaluated how home range estimates varied as a result of the method used and between urban and wild habitats. My results indicated that different home range tools and methods yielded different home range sizes and configurations. Home range sizes were not consistently statistically different from other published, mostly wild, bear home ranges. Additionally, I tried to illuminate how use of the urban area might increase as a result of drought. The Lake Tahoe region and California as a whole suffered a prolonged drought from 2012-2016. Wildlife were expected to seek out anthropogenic resources in close proximity to human habitation to overcome natural food deficits. An uptick in urban use in 2014 was noted and might be attributable to drought conditions. An effort was made to identify patterns in space use as a result of sex and season, and results indicated that home range sizes for females and females with cubs did not differ in size. Additionally, I assessed how models might provide different results between urban and wild areas. During the fall season, overlap with the urban portion of the home range was strongest, and use was even more pronounced during the fall of 2014 as a result of drought impacts. The RSF function included roads, roads with speeds greater than 35 mph, hiking trails, wetlands, known bear conflict areas and elevation. Females with cubs selected for areas of known conflict, which is supported anecdotally by the large number of bear-human conflicts reported by a small number of females with cubs.Finally, human-wildlife conflict has been growing globally and conflicts involving black bears also increased in number and significance throughout the western United States. This trend was particularly evident throughout the Lake Tahoe Basin. After meetings throughout the last decade with many local and regional stakeholders, including the late Senator Dave Cox, the California Department of Fish and Wildlife decided to implement aversive conditioning (AC) in addition to a continued education effort and depredation process allowing lethal removal of nuisance bears. AC was not intended to, nor had it previously been successful in persuading bears to leave urban areas. It had shown success, though, in modifying the behavior of certain bears by scorning bold behavior and rewarding their natural, shy behavior. I studied the effectiveness of using Karelian bear dogs and less-lethal ammunition to condition the behavior of bears. Three protocols were used: soft release, release with dogs, release with dogs and less-lethal ammo. I tested when bears would return to the capture location, reliance on the urban envelope, whether averted bears became more nocturnal, selected a hibernacula further away developed areas, were less winter active, decreased their foraging on anthropogenic resources and usage of known conflict areas. Contrary to expectation, some bears did not return to their capture or release locations. The majority of these individuals had experienced AC, with AC with Dogs appearing to have the greatest effect. Additionally, the return to patch time (BRP) for bears treated with Karelian bear dogs was greater than bears in the Control group for their return to both capture and release locations. Dogs also had the greatest effect on all behavioral proxies examined and bears treated with Dogs seemed to become more nocturnal, less winter active and spent less time in urban areas. These impacts of bear behavior may ultimately reduce the level of conflict with humans. The research presented in this dissertation adds to the growing body of literature on wildlife in the wildlife-urban interface and black bears specifically. Black bear behavioral responses to AC and how they may become less likely to engage in conflict showed promising results. My work suggested that a bear’s ecology living in the wildlife-urban interface may be more complicated and that mixed space use strategies, using both wild and urban areas, appear to be common.